Faktor Penentu Akuntabilitas Pengelolaan Dana Desa: Studi Empiris pada Desa di Kabupaten Kudus - Dennyca Hendriyanto Nugroho; Febra Robiyanto; Ratna Faridotun Naim Pratama (Pusat Riset dan Inovasi Nasional, 2025)
The accountability of village fund management is a crucial obligation for village governments as a form of responsibility for the use of public funds, in accordance with the mandate of Law Number 6 of 2014. This study aims to examine the influence of leadership, clarity of budget objectives, supervision, utilization of information technology, and the village financial system on the accountability of village fund management. The research employed a quantitative method with a survey approach using questionnaires. The sample consisted of 345 respondents who were village officials from 123 villages in Kudus Regency. Data analysis was carried out using multiple linear regression with SPSS version 25. The results show that leadership, clarity of budget objectives, and the use of information technology have a significant positive effect on the accountability of village fund management. In contrast, supervision and the village financial system were found to have no significant impact. These findings highlight the importance of effective leadership, clear budget targets, and the optimization of information technology in achieving accountable village fund management.